(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article provides a scholarly analysis of the foundations of Islamic law, tracing the formation of the discipline, its historical stages, the development of fiqh and usul al-fiqh, as well as the influence of early mujtahids on the evolution of legal reasoning. The study is based on the sources of Islamic law, methods of ijtihad, and the evolution of religious-legal thought.